Physical and technical performance in and after the worst-case scenario in matches of the Chinese Super League of soccer - Fang, Z.; Wang, Z.; Li, X.; Gómez, M.-A.; Liu, H. (Biology of Sport, 2025)
This study aims to investigate the changes in physical and technical performance of professional soccer players during effective playing time after the worst-case scenario (WCS) identified by the high-intensity running (HIR) distance using rolling average. A total of 576 matches (n = 13,298 observations) from the 2019 to 2021 season of the Chinese Super League (CSL) were analyzed by a video tracking system. Generalized mixed linear models were established to determine the mean changes in the value of 7 physical and 24 technical performance-related parameters in the effective playing time from the 5 min of WCS (Peak5) to the initial 5 minutes post-WCS (Post5). Results showed that: (1) For all the players in the Post5 total distance, HIR distance, and Sprint decreased by 16.6% (ES;±99%CL: 0.57;±0.04), 77.2% (2.78;±0.06), and 86.1% (2.11;±0.08), respectively. The number of efforts, average duration, average speed, and average length of HIR declined by 70.8% (2.26;±0.06), 31.7% (0.78;±0.05), 3.1% (0.52;±0.05), and 22.9% (0.83;±0.05), respectively; (2) In the Post5, a substantial decrement in the number (0.23;±0.03), average speed (0.32;±0.06) and average length (0.37;±0.06) of running with the ball, and average speed receiving the ball (0.5;±0.05) was observed for all players. While only trivial changes were detected in all the other technical performance-related parameters. It can be concluded that, in the Post5, there is a temporary decline in physical output and the physical-related technical parameters for players, however, there are no meaningful changes in other technical performancerelated parameters.